Statin treatment and LDL target value achievement in Swiss general practice – a retrospective observational study (Swiss Medical Weekly, 2020)
AIMS Statins decrease the risk of fatal CVD by lowering low-density lipoprotein (LDL) levels. Guidelines suggest that statin treatment strategies should be guided by CV risk, but little is known about statin treatment in Swiss general practice. In this study, we aimed to investigate statin treatment and LDL target achievement rates, including their predictors, in patients treated by Swiss general practitioners (GPs). METHODS Retrospective observational study of statin-treated patients in 2018 using a general practice electronic medical records database. CV risk categories were defined according to the ESC guidelines published in 2016. We used multilevel logistic regression models to find associations between patient and GP demographic factors and LDL target achievement. RESULTS We analysed 11,779 statin-treated patients, of whom 59% were at a high or very high risk of fatal CVD. High-intensity statin treatment was used in 39% of patients, and LDL measurement was performed at least once in 54% of patients. Achievement of LDL target levels across CV risk categories was 36% in very high-risk, 56% in high-risk, and 66% in low-/moderate-risk patients, and generally higher for male patients. CONCLUSIONS Although over half of patients were at a high or very high risk of fatal CVD, the majority did not receive high-intensity statin treatment. Only a third of very high-risk patients achieved LDL target values, and there was a gender gap in LDL target achievement disadvantaging female patients. Results from this study suggest that current treatment may warrant reconsideration in a large proportion of patients treated with statins in Swiss general practice.